Wade Hampton Frost, pioneer epidemiologist, 1880-1938 : up to the mountain - Daniel, Thomas M., 1928- (University of Rochester Press, 2004)
Wade Hampton Frost was the first Professor of Epidemiology at Johns Hopkins University in the first Department of Epidemiology in the United States. A Virginian and a graduate of the University of Virginia, Frost began his remarkable career with two decades of service in the United States Public Health Service. He investigated epidemics of yellow fever, typhoid, polio, streptococcal sore throat, meningitis, and influenza. His greatest contributions during this part of his career were the recognition that mild and asymptomatic childhood polio produced life-long immunity and the development of methods for tracking influenza epidemics. He was recruited to Johns Hopkins in 1919, where, as a Professor at the School of Hygiene and Public Health, he trained many of the future leaders of American public health programs. He made substantial contributions to epidemiologic methodology including developing the concept of an index case during investigations of tuberculosis in Tennessee, the use of life-table methods for estimating secondary attack rates, the use of age cohorts for longitudinal studies, and, in collaboration with Lowell Reed, the first mathematical expression of the epidemic curve. Thomas M. Daniel's biography tells the story of Frost's life and work. Drawing of Frost's personal papers and recorded interviews with his colleagues deposited in the Frost Archives at the University of Virginia Medical Center as well as material from the Fauquier County Heritage Society and Johns Hopkins University, Daniel recounts the story of Frost's life and provides many insights into the personal characteristics of his subject. Daniel also reviews Frost's work, examining his published papers and archived teaching notes to elucidate the scope of and manner in which Frost made his seminal contributions to epidemiology and public health. George Comstock, Emeritus Centennial Alumni Professor of Epidemiology at Johns Hopkins has provided an introduction.Thomas M. Daniel is Professor Emeritus of Medicine.